Fertilizer management practices in potato cultivation: a baseline study for the introduction of GE potato in Bangladesh - Nahiyan, Abu Shamim Mohammad; Islam, Saiful; Islam, Aparna; Rahman, Mohammad Ataur; Hasan, Mohammad Mahmood; Eusufzai, Tasnin Khan; Afreen, Mohsina; Ansarey, Fareyzul Haque; Khan, Tahmina; Uddin, A. F. M. Jamal (Frontiers in Bioengineering and Biotechnology, 2024)
Genetically engineered (GE) crops have the potential to contribute to agricultural sustainability, food security and nutritional enrichment. However, these crops cannot be released for commercial cultivation without undergoing environmental risk assessments (ERA) thus biosafety evaluation. ERA assessments are performed comparatively with their natural non-GE counterparts. As Bangladesh is progressing with GE potato research, the present study aims to collect baseline information on non-GE potato cultivation with an emphasis on current agronomic practices focusing on fertilizer management and farmers’ knowledge base. The survey had three parts, including information on the farmers, information on the potato cultivation practice, especially fertilizer use and lastly, the farmer’s view on GE potato. From 2020 to 2021, data were taken through interviews with experienced growers in four potato growing regions, the Central and Mid-East, North-West, Mid-West, and South-East regions (n=1757) of the country. The study revealed that farmers of all regions used excessive fertilizers than recommended doses, for instance, 67.1% nitrogen fertilizer was applied as an extra dose during potato cultivation in Munshiganj (Central & Mid-East) as compared to the Dinajpur region (North-West). This overuse of nitrogen fertilizer can enhance plant vigor, making them more susceptible to insect attraction and allowing pests easier access to the plants. As a result, the excess dose of nitrogen fertilizer in Munshiganj may act as a catalyst to increase the probability of late blight. The findings also showed that 73.6% of farmers observed unexpected flowering in certain potato cultivars, which corresponded to the higher application of phosphate and potassium fertilizers aimed at late blight control. Furthermore, this study reported infestations of solanaceous weeds, specifically Solanum torvum and Physalis heterophylla, in potato fields. Finally, our findings demonstrated that more than 68.7% of the potato growers have the intention to adopt disease-resistant GE potato as that may reduce the need for excess fertilizers usage thus reducing cultivation costs.